The prognostic impact of BMI on colorectal cancer is stratified by tumor location - Zhang, Zixi; Yan, Xueli; Lu, Yan; Guo, Xiaowen; Jiao, Min; Wang, Weizhong; Sun, Boqian; Zhou, Yi; Hu, Qinglin; Chu, Dake (Frontiers in Oncology, 2022)
Purpose: Recent studies revealed contrasting prognostic roles of body-mass index (BMI) and tumor location in colorectal cancer (CRC). Given that right-sided and left-sided CRC may exhibit inverse impact on outcome and body weight, the present study is to examine whether the prognostic value of BMI and tumor location could be stratified reciprocally. Methods: This prospective, observational study recruited 4,086 patients with diagnosed stage III CRC from 5 independent clinical centers in China. The association of patients’ outcome with BMI and tumor location was evaluated hierarchically by Kaplan-Meier and Cox proportional-hazards model. Results: Although BMI was not associated with outcome within total patients, this association was significantly modified by tumor location. Among left-sided tumors, obesity and overweight was significantly associated with adverse OS and DSS. In contrast, among right-sided tumors, overweight was significantly associated with more favorable OS and DSS compared with normal-weight group. The association of survival with tumor location did not reach statistical significance either. However, hierarchical analysis by BMI revealed that left-sided tumors were associated with more favorable outcome in normal-weight group, while no statistically significant difference in overweight or obese group. Conclusions: BMI and tumor location may have opposing prognostic impact on CRC, stratified by each other, after adjusting for known prognostic factors. These findings are the first to show the interactive prognostic impact of BMI and tumor location, which could be relevant to stratification of patient management.